solve for alpha and beta

Asked by palaksophia | 26th Sep, 2009, 11:12: AM

Expert Answer:

f(x) = ax2 + bx +c

The zeros are given by,

x = (- b ± (b2 - 4ac))/(2a)

Let @ = (- b + (b2 - 4ac))/(2a) and & = (- b - (b2 - 4ac))/(2a)

@ - & = (- b + (b2 - 4ac))/(2a) - (- b - (b2 - 4ac))/(2a)

= (b2 - 4ac)/a ...............................Answer

Generally the difference of the roots is,  ±(b2 - 4ac)/a.

Regards,

Team,

TopperLearning.

 

Answered by  | 26th Sep, 2009, 02:53: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.